Dynamic Process and Damage Evaluation Subject to Explosion Consequences Resulting from a LPG Tank Trailer Accident - Wang, Kan; Liu, Yang; Wang, Hao; Liu, Xiaolei; Jiao, Yu; Wu, Yujian (Processes, 2023)
The involvement of liquefied petroleum gas (LPG), which is highly combustible and explosive, greatly increases risk in road transport. A 3D numerical model was conducted in FLACS, which depicts the dynamic process and variation of combined effects along the multi-directions of LPG explosion under an actual case. With the simulation of scenarios, power-law explosion and fireball models were used to reproduce the results, and the dynamic evolution of specific parameters during the LPG explosion process was analyzed. The results reveal that the LPG explosion’s expansion around the expressway moved along the spaces between obstacles, while conditions at the site of the accident had an enhancement effect on LPG/air mixture accumulation. The propagation trajectory of the shock wave in the horizontal direction presented a regular circle within 623.73 ms, and the overpressure was enough to lead to extensive damage to surrounding structures. Further, shock wave-driven overpressure brought hazards to buildings further afield with multiple peak values. The influence of the LPG explosive fireball evolution is significantly reflected in the injury range of the heat flux; the maximum diameter of the on-site fireball eventually extended to 148.19 m. In addition, the physical effect indicated that the turbulence intensity induced by the surrounding buildings in the accident site significantly promoted the interaction between the shock wave and flame propagation. This research proposes a detailed analysis of damage coupling characteristics caused by an LPG tank trailer explosion integrated with a FLACS-mirrored model, which are useful for blast-resistant design and disposal planning under similar accidental circumstances.